Synthesis of a library of variously modified 4-methylumbelliferyl xylosides and a structure–activity study of human β4GalT7. Issue 45 (8th November 2017) - Dahbi, Samir; Jacquinet, Jean-Claude; Bertin-Jung, Isabelle; Robert, Anne; Ramalanjaona, Nick; Gulberti, Sandrine; Fournel-Gigleux, Sylvie; Lopin-Bon, Chrystel
Abstract : Various modified xylosides were prepared and tested as substrates/inhibitors of human β4GalT7, a key enzyme involved in the biosynthesis of proteoglycans. Abstract : Proteoglycans (PGs) are complex macromolecules that are composed of glycosaminoglycan (GAG) chains covalently attached to a core protein through a tetrasaccharide linker. The biosynthesis of PGs is complex and involves a large number of glycosyltranferases. Here we present a structure–activity study of human β4GalT7, which transfers the first Gal residue onto a xyloside moiety of the linkage region. An efficient and regiocontrolled synthesis of a library of modified analogs of 4-methylumbelliferyl xyloside (XylMU) is reported herein. Hydroxyl groups at the position C-2, C-3 or C-4 have been epimerized and/or replaced by a hydrogen or a fluorine, while the anomeric oxygen was replaced by either a sulfur or a sulfone. The effect of these compounds on human β4GalT7 activity in vitro and on GAG biosynthesis in cellulo was then evaluated.